Integrity of Financial Statement Factors: Intellectual Capital, Independent Commissioner, and Company Size - Suzan, Leny; Mutiah, Noraini Fairuth (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
It is critical to keep financial reporting accurate since it impacts company strategy, confidence from investors and stakeholders, ability to make strategic decisions, availability of funds, and management of reputation. Examining property and real estate companies listed on the Indonesia Stock Exchange between 2018 and 2022, this study seeks to ascertain the effects of company size, intellectual capital, and independent commissioners on the accuracy of their financial statements. This study used descriptive statistics and regression panel data to analyze its data. Independent commissioners, intellectual capital, and company size all have a role in how trustworthy financial statements are, according to the research. The credibility of a company's financial accounts is unaffected by its size. The firm's stance is heavily influenced by intellectual capital, whereas independent commissioners significantly hinder it.